2022
DOI: 10.3390/ijerph19116799
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biological Drugs for Psoriasis: A Drug-Utilization Study Using Tuscan Administrative Databanks

Abstract: Our study aims at providing evidence on patterns of use of biologic drugs for psoriasis in Tuscany, Italy. We conducted a drug-utilization study based on administrative databanks of Tuscany (EUPAS45365) from 2011 to 2019. We selected new users of etanercept, infliximab, adalimumab, ustekinumab, or secukinumab between 1 January 2011 and 31 December 2016. We considered subjects with psoriasis and followed subjects until the end of the study period (three years after the first dispensation of biologic drug for ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(48 reference statements)
2
1
0
Order By: Relevance
“…Feldman’s study highlighted even lower persistence with anti-TNF agents, considering longer follow-up periods at 12, 18, and 24 months. The observed low persistence with apremilast is consistent with previous findings as described by Feldman SR and others [ 31 , 33 ]. These findings suggest multiple factors contributing to poor persistence, including potential drug inefficiency, loss of response over time, and the occurrence of adverse events [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Feldman’s study highlighted even lower persistence with anti-TNF agents, considering longer follow-up periods at 12, 18, and 24 months. The observed low persistence with apremilast is consistent with previous findings as described by Feldman SR and others [ 31 , 33 ]. These findings suggest multiple factors contributing to poor persistence, including potential drug inefficiency, loss of response over time, and the occurrence of adverse events [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings seem to align with previous literature, highlighting low rates of therapy switches [ 31 , 32 , 33 , 34 ]. Specifically, in the Italian context, Giometto et al (2022) reported a low overall switch rate (20%) with anti-IL drugs [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation